Renal simplicity denervation reduces blood pressure and renal injuries in an obesity‐induced hypertension dog model. (20th September 2017) - Zhang, Zhihui; Yang, Kan; Zeng, Lixiong; Wang, Xiaoyan; Jiang, Fenglin; Tu, Shan; Liang, Qishun; Shen, Zhijie
Summary: This study aimed to investigate the effects of renal sympathetic denervation (RDN) on blood pressure, renal function, and renal tissue pathological changes in obesity‐induced hypertensive dogs. Thirty‐two beagle dogs (10‐12 months) were randomized to the control (n=10) and model groups (n=22). High‐fat diet (HFD) was used to establish the obesity‐induced hypertensive model. After 3 months of HFD, 20 animals with successfully induced hypertension were randomized to the RDN (n=10) and sham groups (n=10). Renal artery angiography, body weight, blood pressure, heart rate (HR), and blood and urine biochemistry were determined 1, 3 and 6 months after surgery. Models were killed 6 months after surgery. Pathological changes in the renal artery and renal tissue were assessed. The HFD group had significantly ( P <.05) increased body weight, HR, and blood pressure, and higher levels of urine albumin, serum noradrenaline, and angiotensin II compared with controls. After RDN, blood pressure was decreased compared with baseline and the sham group ( P <.05). In the RDN group, examination of the renal artery and renal tissue showed intact intima of renal artery in the surgical area, renal sympathetic nerve degeneration, necrosis, and dissolution, and widened space between nerve fibres. Hypertension‐induced renal pathological changes were mild to moderate in the RDN group, but severe in the sham group. The control group had normal glomerular structure. In conclusion, RDN can effectively lower blood pressure in obesity‐induced hypertensive dogs, as well as hypertension‐induced renal pathological changes.